Co-solvent selection for supercritical fluid extraction of astaxanthin and other carotenoids from Penaeus monodon waste - Azfar Radzali, Shazana; Baharin, Badlishah Shah; Othman, Rashidi; Markom, Masturah; Abdul Rahman, Russly (Japan Oil Chemists' Society, 2014)
In recent years, astaxanthin is claimed to have a 10 times higher antioxidant activity than that of other carotenoids such as lutein, zeaxanthin, canthaxanthin, and β-carotene; the antioxidant activity of astaxanthin is 100 times higher than that of α-tocopherol. Penaeus monodon (tiger shrimp) is the largest commercially available shrimp species and its waste is a rich source of carotenoids such as astaxanthin and its esters. The efficient and environment-friendly recovery of astaxanthins was ac